NUTRITIONAL AND BIOLOGICAL VALUE OF CAULIFLOWER - Майстер, Ангастасія; Горбатюк, Світлана; Конах, Валентина; Баліцька, Людмила; Слободяник, Галина; Войцехівський, Володимир; Мулярчук, Оксана (SWorldJournal, 2022)
The results of the analysis of valuable nutrients of cauliflower are presented. Significant influence of varietal features on the formation of individual valuable nutrients is revealed. The most valuable varieties are selected according to the studied ind